t+1/3=1

Simple and best practice solution for t+1/3=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for t+1/3=1 equation:



t+1/3=1
We move all terms to the left:
t+1/3-(1)=0
determiningTheFunctionDomain t-1+1/3=0
We multiply all the terms by the denominator
t*3+1-1*3=0
We add all the numbers together, and all the variables
t*3-2=0
Wy multiply elements
3t-2=0
We move all terms containing t to the left, all other terms to the right
3t=2
t=2/3
t=2/3

See similar equations:

| 3((5x+3)×(x-2))^2=18 | | 11x=8x-3-15-6x | | 3(c+4)=4c-6 | | -9+3f=9 | | -18=p+-3 | | 916−2t=5t+916 | | 1.50x+15=19 | | x²+9x-10=0 | | x-35=315 | | w^2+81-18=0 | | -3(4-m)=(2m+1) | | -11j=-220 | | 5(3-x)+2(3-x)=4 | | 9a+5=23 | | 0=2x^+5x-6 | | 38=k/7+34 | | 3k-14-2k=12 | | x-2=5.56 | | 100=10b+10 | | -10+n/13=-2 | | -6(x+1)=-18 | | 4(5x+8)=20x-9 | | 8x=+6=42 | | 4+7y=95 | | 4(2m5)3m=35 | | 5h+12=22 | | 12x+2=10x+40 | | 3k-6=2k+4+k | | -7w+-24=60 | | 2b^2-4b-96=0 | | 9m+8=4m+43 | | c/6+71=79 |

Equations solver categories